Economic characteristics of foresight technologies - Mekhovych, K. S. (Teadmus OÜ, Tallinn, 2025)
The report substantiates that the use of foresight methods in public administration allows creating long-term economic strategies, increasing innovation activity and ensuring the competitiveness of national economies in the global space. At the enterprise level, foresight helps to identify promising market niches, adapt business models to technological changes and minimize the risks of uncertainty.
Keywords: foresight; public administration; methods; technologies; economic strategy; foresight